An assessment on the livelihood of Sto. Angel Multi-purpose cooperative a women's cooperative in Sto. Angel, San Miguel, Iloilo - Villaflor, Romina O.; Ecraela, Lynette E.; Genizera, Darlene (1998)
Much has been said and written about people empowerment and people-centered development, but seldom has it occurred that women's cooperatives are given due consideration. A cooperative is a potential instrument for empowerment and one that is organized for women is an instrument for empowering women, too. The government has launched various strategies in the past, but some of these strategies have only gone halfway in their pursuit of poverty alleviation. It is believed that for development to be genuine, it should serve the interest of the whole population, not just the interest of the dominant class, or gender, for that matter. Thus, an assessment of the livelihood projects and programs of the Sto. angel Multi-Purpose Cooperative, a women's cooperative, will validate the issue of women empowerment in Sto. Angel, San Miguel, Iloilo - rural community. The researchers would like to find out if this is really happening in the context of rural communities where massive poverty is more prevalent. But intending to do more than this, the researchers particularly want to find out if women are empowered, and hence, a part of the so-called people-centered development.
[Research Paper] (Mgt 200 - Management Research) -- Iloilo City : UPV-CM, March 19, 1998.